Preferensi Parameter Oseanografi (SPL dan klorofil-a) Terhadap Hasil Tangkapan Ikan Cakalang di Perairan Pulau Misool dan Fakfak - Mustasim Mustasim; Mukti Zainuddin; Syafruddin; Dian Sutono (Jurnal Airaha, 2019)
This study aims to analyze preference oceanographic parameters (SST and chlorophyll-a) of the Skipjack in the Misool dan Fakfak Waters. The research was conducted in March-May 2015 in the Misool dan Fakfak Waters, the data in the form of catch March to May 2015, SST and chlorophyll-a obtained from satellite imagery MODIS-Terra. Data were analyzed using Softwere ArcGis 10.2, ENVI 5.1. and softwere ORIGIN Versi 8.5.1. The results of the study showed that the preferences of the SPL and chlorophyll-a concentration of the Skipjack in the month of March to May, 2015 in the range of 29.50 to 30.50°C and chlorophyll-a concentration of about 0.10 to 0.20 mg/m3.